Design and Development of An Information System for Indemnity Claim Box Recapitulation Using SDLC Method at Mandiri Inhealth Insurance - Yumansyah, Qori; Fatchan, Muhamad; Turmudi Zy, Ahmad (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The recapitulation of indemnity claim box system is an ongoing procedural development activity aimed at producing a new system. This activity is undertaken once the system analysis phase has been completed. Based on the results of the current system analysis discussed in the previous section, this paper presents the outcomes of the new system. The performance of the new system is expected to address several issues related to claim data recapitulation. The design of the Indemnity Claim Box Recapitulation system can be applied to reduce the potential for missing documents, simplify reporting, and ensure easy, fast, and accurate access. Implementation testing can assist users and leaders in the claim data recapitulation process.